2001
DOI: 10.1002/mas.10011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nucleic acids by on‐line liquid chromatography–Mass spectrometry

Abstract: The numerous problems posed by modern biochemistry, biology, and medicine, as well as the growing significance of genetic engineering require the application of fast and reliable methods of utmost sensitivity and selectivity for the analysis of nucleic acids. High-performance liquid chromatography (HPLC) and mass spectrometry (MS) represent established analytical techniques for the characterization and structural elucidation of single- and double-stranded nucleic acids, ranging in size from a few nucleotides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
129
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 113 publications
3
129
0
1
Order By: Relevance
“…Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI -TOF -MS) [13] and electrospray ionization (ESI) mass spectrometry [14] have revolutionized the analysis of nucleic acids and other biomolecules. It has been shown that ESI can be routinely coupled to (liquid) chromatography to provide separation of DNA molecules as well as sample clean-up [15]. ESI can be used to detect large molecules (> 20 kDa) and was applied to analyse small PCR products [16,17].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI -TOF -MS) [13] and electrospray ionization (ESI) mass spectrometry [14] have revolutionized the analysis of nucleic acids and other biomolecules. It has been shown that ESI can be routinely coupled to (liquid) chromatography to provide separation of DNA molecules as well as sample clean-up [15]. ESI can be used to detect large molecules (> 20 kDa) and was applied to analyse small PCR products [16,17].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Another approach is introducing liquid chromatography (LC) for separation. LC provides an on-line separation of the analytes from coexisting substances and does not require a laborious sample preparation prior to ionization 21,22 . Application of LC/ESI-MS genotyping for differentiation of pathogen species, single-nucleotide polymorphisms and short tandem repeats has been reported using a capillary polymer-monolith column that can separate longer oligonucleotides 1,21,[24][25][26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the proofreading activity of the applied polymerase system, mismatches between the primer and the target sequence located at the last or the second last base at the 3=-end of primers were corrected and detected within the corresponding amplicons. E lectrospray ionization mass spectrometry (ESI-MS) represents a powerful method for the characterization of nucleic acids [1,2]. Molecular mass determination of intact DNA molecules with lengths up to several hundred base pairs [3][4][5][6] is accomplished with high-performance, which enables the detection of sequence variations directly upon analyzing polymerase chain reaction (PCR) amplified sequences.…”
mentioning
confidence: 99%
“…Even moderate concentrations of salts are known to detract from the ionization efficiency of nucleic acids and need to be removed (for a detailed discussion of this problem, please refer to references [1,8,9]. In this context, chromatography was shown to be one of the most efficient nucleic acid purification techniques available [9].…”
mentioning
confidence: 99%